Microbial Community Structure Affects Marine Dissolved Organic Matter Composition - Kujawinski, Elizabeth B.; Longnecker, Krista; Barott, Katie L.; Weber, Ralf J. M.; Kido Soule, Melissa C. (Frontiers in Marine Science, 2016)
Marine microbes are critical players in the global carbon cycle, affecting both the reduction of inorganic carbon and the remineralization of reduced organic compounds back to carbon dioxide. Members of microbial consortia all depend on marine dissolved organic matter (DOM) and in turn, affect the molecules present in this heterogeneous pool. Our understanding of DOM produced by marine microbes is biased towards single species laboratory cultures or simplified field incubations, which exclude large phototrophs and protozoan grazers. Here we explore the interdependence of DOM composition and bacterial diversity in two mixed microbial consortia from coastal seawater: a whole water community and a <1.0-μm community dominated by heterotrophic bacteria. Each consortium was incubated with isotopically-labeled glucose for 9 days. Using stable-isotope probing techniques and electrospray ionization Fourier-transform ion cyclotron resonance mass spectrometry, we show that the presence of organisms larger than 1.0-μm is the dominant factor affecting bacterial diversity and low-molecular-weight (<1000 Da) DOM composition over this experiment. In the <1.0-μm community, DOM composition was dominated by compounds with lipid and peptide character at all time points, confirmed by fragmentation spectra with peptide-containing neutral losses. In contrast, DOM composition in the whole water community was nearly identical to that in the initial coastal seawater. These differences in DOM composition persisted throughout the experiment despite shifts in bacterial diversity, underscoring an unappreciated role for larger microorganisms in constraining DOM composition in the marine environment.